Contextual Learning as a Means to Improve Elementary School Students' Mathematical Literacy Skills - Hidayana, Rizki Apriva; Lianingsih, Nestia (Research Collaboration Community (RCC), 2025)
Mathematical literacy in the Programme for International Student Assessment (PISA) emphasizes students’ ability to analyze, justify, and effectively communicate ideas, as well as to formulate, solve, and interpret mathematical problems across various forms and contexts. The PISA assessment focuses on real-life problems rather than solely on typical classroom-based questions. Based on cognitive development stages, elementary school students are generally in the concrete operational stage, which means they require tangible objects that can be perceived through the senses. Since mathematics learning tends to be abstract, students need support in the form of media and teaching aids to clarify concepts delivered by the teacher, making them easier to understand. Mathematics instruction is expected to provide an integrated, comprehensive, and holistic understanding of the material. This understanding not only fulfills the demands of mathematical content but also offers practical benefits to students. This aligns with the contextual learning approach, which emphasizes active student engagement throughout the learning process, enabling them to discover concepts independently and relate them to real-life situations. Contextual learning is carried out through four main stages: providing motivation, conceptual understanding, application, and assessment—all of which are grounded in the core components of contextual learning.